Intersektionale Solidaritäten Beiträge zur gesellschaftskritischen Geschlechterforschung - Mertlitsch, Kirstin; Hipfl, Brigitte; Kumpusch, Verena; Roeseling, Pauline (Verlag Barbara Budrich, 2024)
Allyship, network, and community: these concepts have recently returned to the center of (queer) feminist, gender-specific, and intersectional theories and practices. The book's contributions address successes and challenges of queer-feminist, anti-racist, and intersectional alliances in their local, regional, and global interconnectedness, as well as examples of queer, non-heteronormative, inter*, and trans* collectives and solidarities.